Starring Nero as Nero: poetry, role-playing and identity in Juvenal 8.215-21 - Cowan, R (Brill, 2009)
Juvenal's synkrisis between Orestes and Nero climaxes with the statement that the former never played Orestes; the implied antithesis, that Nero did play Nero, gains point from the princeps' practice of wearing masks resembling his own face. This blurring of the distinction between 'playing Nero' and 'playing Orestes' problematizes the princeps' identity. This problematization is furthered by the peculiarities of Orestes, who in various tragic plots repeatedly either plays other roles or is himself impersonated. This is part of Satire 8's wider exploration of identity as undetermined by ancestry and the inadequacy of names as signifiers. The further statement that Orestes never wrote a Troica is illuminated by its intertextual engagement with Callimachus Epigr. 59 G-P, in which the poet's loss of his 'Pyladeses' through writing a play contrasts with Orestes' omission of this final act of madness. The Callimachean Orestes thus keeps distinct the roles of tragedian and tragic hero, poet and character, thereby foregrounding Nero's failure to maintain this distinction. By blurring his identity with that of Paris in both his epic and his alleged burning of Rome, Nero confuses the categories of artist and perpetrator, creator and character, just as he and Orestes confuse those of actor and role.